Generation of Compost Fertilizers from Banana Stem using Poultry Droppings and Industrial Sewage Sludge as Activators - Awolusi, Oluyemi Olatunji (2015)
Banana pseudostem was composted using poultry droppings and industrial sewage sludge as activators. The specific objectives were to isolate and identify some of the microorganisms involved in the composting, assess the bacterial and fungal dynamics during composting process, determine the population of coliforms in the matured compost, determine the effect of activators on the quality of compost generated, and determine the quality of end-product (compost). This was with a view of assessing if a sanitarily-safe quality organic fertilizer can be produced from banana pseudostem.